Modeling borderline personality traits based on attachment: the mediating role of self-differentiation and emotional dysregulation - Shirazi, Effat; Ghasemi Motlagh, Mehdi; Esmaeeli Shad, Behrang; Bakhshipoor, Abolfazl (Applied Family Therapy Journal (AFTJ), 2022)
Aim: The aim of this study was to model borderline personality traits based on attachment: the mediating role of self-differentiation, and emotional dysregulation. Methods: The present study is descriptive and correlational (using structural equation modeling). The statistical population studied in this study included all male and female undergraduate and graduate students of Tehran Azad University who were studying in the 2019-20 academic year. The sample of the present study included 370 people who were selected by purposive sampling. Data were obtained using the Borderline Personality Questionnaire (Leishnring, 1999), the Revised Relationships-Relationship Structure Questionnaire (Fraley, Valero Brennan, 2000), the Scorne and Friedlander Self-Differentiation Questionnaire (1998), and the Gretz and Roemer Emotion Regulation Difficulty Scale. (2004). In the present study, the mean, standard deviation, correlation and normality of the distribution of research variables were investigated using descriptive statistics. Also, in order to analyze the data and answer the research questions, the structural equation modeling method is used, which after confirmatory factor analysis - in the measurement model section, in the structural equation model section, the causal relationships between latent variables are examined. In the model part of the structural function, the intensity of causal relationships (direct, indirect and total) between latent variables and the amount of variance explained in the whole model is specified. SPSS and Amos software version 21 were used for this purpose. Results: The results showed that attachment (β=0.41), self-differentiation (β=0.24), and emotion regulation (β=0.31) had a direct effect on borderline personality symptoms (P